Tissue Regeneration Enhancer Elements: A Way to Unlock Endogenous Healing Power. Issue 1 (28th November 2018) - Yang, KaHoua; Kang, Junsu
Abstract: Regenerative capacity is widespread throughout almost all animal phyla. However, the distribution pattern remains incompletely understood. Various examples show that very closely related species display different regenerative capacities. Why and how have diverse regenerative capacities evolved across species? One prevailing thought in the field of regeneration is that most regeneration‐associated factors are evolutionarily conserved, suggesting the existence of an innate tissue regeneration ability in all species. However, its regulation is differentially controlled in distinct species, resulting in heterogeneous regenerative capabilities. In this review, we discuss regeneration‐associated enhancers, the key cis ‐regulatory elements controlling gene expression, their underlying molecular mechanisms, and their influence on regenerative capacity. Understanding the regulatory mechanisms of regeneration enhancers can provide fundamental insights into tissue regeneration and further help us develop therapeutic strategies to unlock latent healing powers in humans. Developmental Dynamics 248:34–42, 2019. © 2018 Wiley Periodicals, Inc. Key Findings: Regenerative capacity is widespread throughout almost all animal phyla, but the distribution pattern remains incompletely understood. Because most regeneration‐associated factors are evolutionarily conserved, the key of diverse regenerative capacity is not the presence or absence of regeneration‐driving genes, but in the mechanisms controlling activation of these genes after injury. In this review, we discuss regeneration‐associated enhancers, the key cis‐regulatory elements controlling gene expression, their underlying molecular mechanisms, and their influence on regenerative capacity.